2019
DOI: 10.1101/544320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The chromatin structuring protein HMGA2 influences human subtelomere stability and cancer chemosensitivity

Abstract: 4The transient build-up of DNA supercoiling during the translocation of replication forks 3 5 threatens genome stability and is controlled by DNA topoisomerases (TOPs). This crucial 3 6 process has been exploited with TOP poisons for cancer chemotherapy. However, 3 7 pinpointing cellular determinants of the best clinical response to TOP poisons still remains 3 8 enigmatic. Here, we present an integrated approach and demonstrate that endogenous and 3 9 exogenous expression of the oncofetal high-mobility group A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(46 citation statements)
references
References 66 publications
7
39
0
Order By: Relevance
“…The clinical data revealed that HMGA2 expression in leukemic cells in vivo is an independent negative predictor of disease relapse and patient survival (Marquis et al , ). Taken together with our previous HMGA2 studies investigating TOP1 poisons and DNA synthesis inhibitors (Ahmed et al , ; Yu et al , ), our current study strongly enforces the clinical importance of HMGA2 as a prognostic therapeutic marker in the clinic and as an important drug target.…”
Section: Introductionsupporting
confidence: 84%
See 4 more Smart Citations
“…The clinical data revealed that HMGA2 expression in leukemic cells in vivo is an independent negative predictor of disease relapse and patient survival (Marquis et al , ). Taken together with our previous HMGA2 studies investigating TOP1 poisons and DNA synthesis inhibitors (Ahmed et al , ; Yu et al , ), our current study strongly enforces the clinical importance of HMGA2 as a prognostic therapeutic marker in the clinic and as an important drug target.…”
Section: Introductionsupporting
confidence: 84%
“…Our previous studies have shown that HMGA2 functions as a replication fork chaperone when replication is challenged by the DNA synthesis inhibitor HU (Yu et al , ). However, HMGA2 differentially affects the genotoxic efficacy of the clinically relevant TOP1 poison irinotecan/SN38, and we mechanistically ascribed these different phenotypic outcomes of drug treatment to ternary complex formation between HMGA2, TOP1, and scDNA substrates (Ahmed et al , ). Here, by employing our four previously established cancer cell models, we first investigated whether HMGA2 affects DNA damage caused by the clinically relevant TOP2 poison Etop.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations